Pemberdayaan Kader Kesehatan Dalam Pencegahan Dan Penatalaksanaan Stunting Melalui Edukasi Dan Optimalisasi Pemanfaatan Pangan Lokal Di Wilayah Puskesmas Tamansari Kota Tasikmalaya - Kamiel Roesman Bachtiar; Salsabila Adlina; Adinda Putri Amanda (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Tasikmalaya City is included in yellow status for stunting, which is the 5th highest in West Java. One of the areas with the highest stunting cases in the city of Tasikmalaya is the Tamansari Community Health Center with a total of 332 stunted toddlers. The partner in this service activity is UPTD Tamansari Community Health Center. Tamansari Community Health Center UPTD oversees 4 sub-district areas, namely Setiawargi, Mulyasari, Sukahurip and Setiamulya. Mulyasari sub-district is the sub-district with the highest number of short and very short toddlers when compared to other sub-districts. Among them, there are 59 very short toddlers and 273 short toddlers in the Toddler Weighing Month (BPB) February 2023. The aim of this community service is directly to increase the knowledge of certain community groups, namely health nutrition cadres, which in health promotion science are referred to as secondary targets in terms of preventing stunting in toddler. When carrying out activities, the delivery of material is carried out by means of presentations using audio-visual technology and is equipped with the delivery of educational materials. Apart from that, to support activities, demonstrations were held on making tempeh and processing tempeh nuggets as MPASI to prevent and overcome stunting. During the evaluation process, the pre-test results showed a score of 59.2%, indicating that the target did not really understand the prevention and management of stunting. The post-test results showed that 93.8% of cadres' knowledge and awareness increased regarding stunting and the benefits of tempeh as a functional food to prevent stunting.